2002
DOI: 10.1080/02678290110113513
|View full text |Cite
|
Sign up to set email alerts
|

Ordering of a lateral crown ether and terminal short POE chains in some symmetrical nematogens by 13 C NMR

Abstract: A lateral crown ether fragment can be introduced on symmetrical mesogens containing only three aromatic rings. The replacement of the terminal alkoxy chains by chains containing oxyethylene units decreases the melting and clearing temperatures allowing one to obtain nematic compounds near room temperature. These compounds dissolve LiBF 4 salt only to a small extent, but the nematic arrangement, is thereby destroyed. The carbon chemical shift anisotropy and the local C-H bond order parameters were obtained for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…446−450 On the other hand, mesomorphism was lost upon addition of small amounts of LiBF 4 to some derivatives with a lower shape anisotropy. 451 Yoshio et al mentioned a short-range nematic phase for an equimolar mixture of an IL ([C 2 mim][BF 4 ]) with a neutral, hydroxyl-terminated LC. 215 Yousif et al, Al-Dujaili and coworkers, and Tong et al reported nematic mesomorphism for some ionic polymers.…”
Section: Liquid-crystalline Ionic Liquids?mentioning
confidence: 99%
See 1 more Smart Citation
“…446−450 On the other hand, mesomorphism was lost upon addition of small amounts of LiBF 4 to some derivatives with a lower shape anisotropy. 451 Yoshio et al mentioned a short-range nematic phase for an equimolar mixture of an IL ([C 2 mim][BF 4 ]) with a neutral, hydroxyl-terminated LC. 215 Yousif et al, Al-Dujaili and coworkers, and Tong et al reported nematic mesomorphism for some ionic polymers.…”
Section: Liquid-crystalline Ionic Liquids?mentioning
confidence: 99%
“…This is not only due to the “straightening” of these chains by metal ion complexation; the stacking into columns also originates from the sequential electrostatic interactions between the ionic moieties in the direction of the columnar axes. Nevertheless, several examples of low molar mass thermotropic ILCs displaying a nematic phase, or a (not commonly observed) columnar nematic phase, can be found in the literature. ,,,,, [Remark: The quaternary ammonium halide salts based on tris­( n -octadecyl)­amine that were originally claimed to show a nematic phase were later reported to show a SmA phase. , ] Veber and co-workers proposed that the formation of the N C phase by some tricatenar dithiolium salts can be rationalized by the fact that the columns in the lower-temperature Col hex and Col rec phases are stabilized by ionic interactions, so that the 2D hexagonal lattice can “melt” without complete destruction of the columns. , Several neutral nematogenic calamitic LCs with a crown ether moiety and/or short oligo­(ethylene oxide) chains were found to dissolve large amounts of LiBF 4 , NaOTf, or sodium picrate (with complexation of the alkali metal cations by the crown ether moiety if present) and still exhibit a nematic phase. On the other hand, mesomorphism was lost upon addition of small amounts of LiBF 4 to some derivatives with a lower shape anisotropy . Yoshio et al mentioned a short-range nematic phase for an equimolar mixture of an IL ([C 2 mim]­[BF 4 ]) with a neutral, hydroxyl-terminated LC .…”
Section: Thermotropic Ionic Liquid Crystals (Ilcs)mentioning
confidence: 99%
“…24,27,28,32 When other structural features are added to this, as for instance, a lateral crown-ether inserted in one of the phenyl rings, the characteristic patterns that establish the position and orientation of the crown-ether are clearly observed. 33 In other examples of different molecular shapes such as thiophene incorporated as a part of the core unit, it is possible to obtain a quick and reliable initial estimate of the alignment from the 2D spectra. 34,35 In this work, we explore using 13 C-1 H dipolar couplings in the nematic phase to provide ordering and orientational information in specically designed nematogens.…”
Section: Introductionmentioning
confidence: 99%
“…From 1D and 2D spectral studies, it is observed that the four carbons (A–D) of the lateral hexyl chain which are nearer to the thiophene ring showed an increase in chemical shifts, whereas the rest of the two carbons, i.e., one methylene and one methyl, showed a decrease. Fung and co-workers , as well as Bayle and co-workers , have extensively studied the 13 C NMR of mesogens in which aliphatic chains are placed at a lateral position of the core. On the basis of the chemical shifts in the mesophase, they interpreted the data with respect to the mean orientation of the chain along the long molecular axis.…”
Section: Resultsmentioning
confidence: 99%
“…In cases where a CH 2 group adopts trans conformation, the chemical shift values are found to decrease in contrast to their solution values, whereas the methylene groups with preferred cis conformation showed a reverse trend. On the basis of these literature studies, and also taking into consideration the chemical shift trends of the chains of HT8, it is concluded that most of the carbons of n -hexyl chain are in cis conformation, while the E and F carbons are in trans conformation. For terminal alkoxy chains, the methylene as well as methyl carbons are in fully extended trans confirmation because the alignment-induced shift (AIS) values are found to be negative.…”
Section: Resultsmentioning
confidence: 99%